2013
DOI: 10.4209/aaqr.2012.04.0095
|View full text |Cite
|
Sign up to set email alerts
|

SEM-EDX Characterization of Individual Coarse Particles in Agra, India

Abstract: Aerosol samples were collected during winter and summer season in Agra, India. The mass concentrations of TSP ranged from 206.1-380.5 μg/m 3 with the average concentration of 306.1 μg/m 3 . The seasonal average concentrations of TSP were 273.4 ± 85.5 μg/m 3 in summer and 338.6 ± 89.1 μg/m 3 in winter. The high levels of mass concentration during winter may be attributed to different emission sources and meteorological conditions at this time of year. The morphology, size and elemental composition of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 69 publications
8
67
0
2
Order By: Relevance
“…SEM equipped with energy-dispersive X-ray spectrometry (EDX) is an effective approach for identifying the surface composition (elemental mapping) of individual particles with diameters greater than 100 nm. The mixing characteristics of different constituents in the surface layer of the particle can be obtained from information on the shape and chemical composition by SEM-EDX (Barkay et al, 2005;Laskin et al, 2006;Pachauri et al, 2013).…”
Section: Analytical Techniques For Particle Mixing Statementioning
confidence: 99%
“…SEM equipped with energy-dispersive X-ray spectrometry (EDX) is an effective approach for identifying the surface composition (elemental mapping) of individual particles with diameters greater than 100 nm. The mixing characteristics of different constituents in the surface layer of the particle can be obtained from information on the shape and chemical composition by SEM-EDX (Barkay et al, 2005;Laskin et al, 2006;Pachauri et al, 2013).…”
Section: Analytical Techniques For Particle Mixing Statementioning
confidence: 99%
“…Electron scanning microscopy coupled with energy dispersive spectrometer (SEM-EDS) analysis can provide substantial information on the elemental composition, mineral types, size distribution, and morphology of the airborne particle, which cannot be achieved by bulk chemical analysis alone (Sharma and Srinivas 2009;Srivastava et al, 2009;Pachauri et al, 2013). SEM-EDS is an analytical method for surface elemental analysis, with a potential detection limit of 0.1-0.5 wt.% for most elements (Haley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some samples show high concentrations of carbon and oxygen as the main elements in EDS spectrum. These are presented in previous studies as characteristics of organic biogenic particles that can be identified easily (Srivastava et al, 2009;Wang and Luo, 2009;Pachauri et al, 2013;Singh et al, 2014). Sometimes these particles are found in clusters.…”
Section: Surface Morphologymentioning
confidence: 99%
“…The results showed that the particles are round, flaky, spherical and irregular shapes. Depending on the elemental composition and observed shapes the particles were divided into two groups (Wang and Luo, 2009;Pachauri et al, 2013). i) Soil dust particles: these particles possess crystalline or irregular shape shown in Fig.…”
Section: Surface Morphologymentioning
confidence: 99%